Haven-Garden System: an Alternative Garden for Temperate-Plants with Microcontroller Application - Saadah Aris Fadzallah, Maryam; Mohd Sani, Maizura; Mohd Hussain, Mashitah; Kassim, Murizah (International Journal of Engineering and Technology, 2018)
Based on the concept of current commercialized greenhouse, a simple system is created to control the modified greenhouse into a â€œsheltered-gardenâ€. This modified greenhouse is made to be different from the conventional ones in terms of its size and control system. The size is designed to fit a normal garden instead of a crop, and the system conceived to be low-cost thus much simpler. Named as Haven-Garden, the system is composed of a PIC16F877A microcontroller via programming language written using PIC Simulator IDE which controls curtain, light sensors, exhaust fan, LCD, LEDs and temperature sensor. All these components are integrated to create a controlled environment in ensuring the necessities of temperature, lighting, humidity, and carbon dioxide (CO2) are delivered adequately to the plants. In this study, the system has the ability to make decisions in providing necessary light intensity needed by controlling the openness of the curtain in the Haven-Garden according to the light radiates by the sun. On the other hand, the conventional light controller does not have the ability to solve this kind of issues, and can only be seen as in big greenhouse project and higher scope of crops to be covered. Therefore, this study identifies a design of a simple and low-cost system integrated with hardware circuit of automated controller using PIC16F877A microcontroller, controlling various parameters inside the â€œalternative gardenâ€. A system was successfully been created as an alternative to a contemporary garden but with far more beneficial as it helps in managing all the plantsâ€™ necessities thus organizing the ownerâ€™s time better. In this study, tests cases have illustrated that dynamic control method could be a suitable alternative method compared to conventional control methods that could save electricity consumption and offers ease of use to human being. The input variables were indoor lighting, inference from outdoor lighting, and temperature while the output variables were the required illumination to achieve the standard; presented in LED lighting, an exhaust fan to control the temperature and humidity, curtain to eliminate excessive light from direct sunlight and an LCD to monitor the temperature inside the Haven-Garden for more effectiveness.Â Â Â